Behavioural Economics and Consumer Decision-Making in the Age of Artificial Intelligence (AI), Data Science, Business Analytics, and Internet of Things (IoT) - Yuki Haruto Yamamoto (Social Science Chronicle)
This research paper examines the transformative impact of behavioral economics on consumer decision making in an era where artificial intelligence (AI), data science, business analytics, and the Internet of Things (IoT) are increasingly influential. These technologies, particularly IoT-enabled “servgoods,” allow for a seamless blend of products and services, fostering intelligent, adaptive, and personalized consumer interactions that fundamentally shift traditional consumer behaviour models. AI-powered systems equip businesses with capability to anticipate consumer preferences and adjust offerings instantaneously, creating a dynamic interplay of digital, economic, and psychological factors that re-shape engagement strategies. Leveraging Big Data and sophisticated analytics, companies achieve greater marketing precision and data-driven insights, leading to highly personalized consumer engagement that aligns with individual preferences. However, while AI and IoT facilitate more efficient and engaging consumer experiences, they introduce complex ethical and practical concerns, particularly around data privacy, algorithmic fairness, and maintenance of consumer trust. The integration of behavioral economics with these technologies presents unique challenges for decision-makers, emphasizing the urgent need for ethical frameworks to guide the use of predictive analytics and algorithm-driven personalization. The convergence of AI with behavioral economics is therefore critical for both understanding consumer behavior and optimizing it in a manner that respects ethical boundaries. This paper underscores the significance of these technological advancements and their alignment with behavioral economics principles, recognizing their potential to profoundly influence, and responsibly steer, consumer decision-making in the digital age.